Cyber Security Practices in Public Universities in South-East Nigeria - Chikwendu, Chilaka Stephen; Oli, Nneka Perpetua (Practicum Psychologia, 2024)
The study examined cyber security practices in public universities in south-east Nigeria. Different public universities are employing various forms cyber security practices in order to protect their information from being compromised by cyber-attacks. This study seeks to find out the cyber security practices these public universities put in place to protect their cyber space. A mixed methods research design was adopted in the study. The sample size of the study was 985. Quantitative and qualitative instruments were used to collect data in the study. A questionnaire was developed to collect quantitative data, while an IDI Guide was used to collect the qualitative data. The data were processed with Statistical Package for Social Sciences (SPSS) version 20. Descriptive statistics, such as simple percentages, frequency tables, and graphic illustrations, were used to analyze the quantitative data. The qualitative data were analyzed using content analysis. Findings from the study show that password protection is the most common cyber security practice employed by public universities in southeast Nigeria to protect data/information at their disposal from cyber-attacks. The study recommends that universities that do not have cyber security practices should come up with one for their employees. The universities should design and circulate clearly articulated cyber security practices that will guide staff conduct over the cyber space whenever they are working with university computers, gadgets or platforms.